2021
DOI: 10.1186/s12884-021-03947-7
|View full text |Cite
|
Sign up to set email alerts
|

“What kind of man gets depressed after having a baby?” Fathers’ experiences of mental health during the perinatal period

Abstract: Background To date, information and support has been focused on mothers, with evidence that healthcare professionals overlook fathers’ mental health, and that fathers receive little or no support for themselves during the perinatal period. However, recently, fathers’ mental health has become an area of interest. Methods This study explored the support fathers receive for their own mental health during the perinatal period. A qualitative questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 45 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…The father needs to be prioritized during the perinatal period, and the health professional should aware that fathers also needs the supports, to developing mental health problems in both parents . This case can be facilitated by increasing capacity and awareness among health professionals and service systems (Hambidge et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The father needs to be prioritized during the perinatal period, and the health professional should aware that fathers also needs the supports, to developing mental health problems in both parents . This case can be facilitated by increasing capacity and awareness among health professionals and service systems (Hambidge et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The inability to manage stress and depression properly can lead to acts of violence in the child which results in the formation of the child's personality, as well as the emergence of feelings of failure to become a new father. Postpartum depression in fathers often occurs in 4-25 percent of new fathers during the first 12 months after birth, but due to lack of awareness and recognition of symptoms, the prevalence rate at the level of depression ranges from 24 to 25 percent for men with partners who experience maternal postpartum depression within 12 months after birth (Hambidge et al, 2021). The appearance of depressive symptoms in the father due to the presence of a linkage with post partum deprertion of the mother.…”
Section: Stress and Depression Of Being New Fathermentioning
confidence: 99%
“…As fathers have highlighted the challenges that they experience trying to gain information and support while engaging with the maternity services (Hambidge et al ., 2021 ), social media and online interventions could potentially serve as effective channels through which mental health awareness and supports could be promoted. Previous research has found that fathers seek health and support information online (Jaks et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, further support is needed to address paternal depression explicitly, especially given the findings of this study. In the UK, NICE ( National Institute for Health and Care Excellence[NIHCE], 2009 ) have made recommendations for how to treat depression, yet there are no specific guidelines for fathers despite growing evidence that men may experience depression differently to women ( Hambridge et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%